Financial Exclusion in Rural and Urban Contexts in Poland: A Threat to Achieving SDG Eight? - Sergio Luis Náñez Alonso; Javier Jorge-Vazquez; Miguel Ángel Echarte Fernández; Konrad Kolegowicz; Wojciech Szymla (Land, 2022)
Financial inclusion, which consists of having a financial system that is easily accessible to citizens, is identified by various international organizations such as the new UN Agenda 2030, as a priority objective. This objective is particularly relevant in rural areas, where access to these services is more difficult, as citizens have to travel several kilometers to access them. In this study, we analyze the current situation of the Polish financial sector in terms of its accessibility, in order to measure the degree of financial inclusion. For this purpose, we use three combined methodologies. Initially, a data extraction from the Central Bank of Poland was carried out. Subsequently, three methodologies are applied to calculate financial inclusion. First, we apply the criteria of the Financial Access Survey (FAS) of the International Monetary Fund. Secondly, the Access to Cash Index (ACI) methodology by calculating a score that describes the access to banking services according to certain items. Finally, we applied the nearest neighbor methodology to detect in each voivodship those points where it is most difficult (measured in km distance) to access banking services. Some areas, especially in rural areas of the different voivodeships, present certain problems when it comes to accessing banking services. Therefore, the fulfillment of SDG 8.10 will be more difficult to achieve in these areas. The public authorities must pay attention to this, in order to reach the commitments acquired with the 2030 agenda, in terms of financial inclusion.